2012
DOI: 10.4081/rg.2012.e12
|View full text |Cite
|
Sign up to set email alerts
|

Geological evidence of tsunamis and earthquakes at the Eastern Hellenic Arc: correlation with historical seismicity in the eastern Mediterranean Sea

Abstract: Sedimentary stratigraphy determined by trenching in Dalaman, south-western Turkey, revealed three sand layers at a distance of approximately 240 m from the shoreline and at elevations of +0.30, +0.55 and +0.90 cm. Storm surge action does not explain the features of these deposits that show instead typical characteristics of tsunami deposition. The sand layers correlate with historical tsunamis generated by large earthquakes which ruptured the eastern Hellenic Arc and Trench in 1303, 1481 and 1741. Accelerator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…9c). Although sedimentary traces of this tsunami were detected by Alpar et al (2012) and Papadopoulos et al (2012) in the sequence of Dalaman Plain ("Da" in Fig. 2a), and by Avşar (2019) in Ölüdeniz Lagoon, it was not detected by other studies carried out in the Aegean Sea (Di, Li, Th, DG, Go and Re in Fig.…”
Section: Extended Summarymentioning
confidence: 71%
“…9c). Although sedimentary traces of this tsunami were detected by Alpar et al (2012) and Papadopoulos et al (2012) in the sequence of Dalaman Plain ("Da" in Fig. 2a), and by Avşar (2019) in Ölüdeniz Lagoon, it was not detected by other studies carried out in the Aegean Sea (Di, Li, Th, DG, Go and Re in Fig.…”
Section: Extended Summarymentioning
confidence: 71%
“…On 8 August AD 1303 a major earthquake with magnitude ∼ M w 8 located between Crete and Rhodes islands ( Fig. 1) generated a tsunami that greatly damaged the coastal cities of the eastern Mediterranean (Ambraseys, 2009;Papadopoulos et al, 2014). In 1329 Abu-El Fida (1907) reported that the Alexandria city and the Nile Delta were flooded and many houses were damaged in Cairo and northern Egypt.…”
Section: Major Historical Tsunamis Of the Mediterranean Coast Of Egyptmentioning
confidence: 99%
“…Minoura et al (2000) described tsunami deposits with volcanic ashes along the coast on Crete (Greece) that correlate with the Thera (Santorini) eruption in the late Minoan period (1600-1300 BC). Papadopoulos et al (2012) documented three paleotsunami layers attributed to the AD 1303, AD 1481 and AD 1741 historically documented tsunamis in Dalaman (southwestern Turkey). Using granulometry, XRD, XRF, and FT-IR, Tyuleneva et al (2018) identified two sedimentary events offshore of Casearea (Israel) that may correlate with landslide tsunamis in AD 749 and 5700 BP (Chalcolithic cultural period).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations